PELAKSANAAN EDUKASI KADER DASAWISMA DI KOTA ADMINISTRASI JAKARTA TIMUR MENGENAI VAKSINASI PADA KONDISI DENGAN KOMORBID: Pelaksanaan Edukasi Kader Dasawisma Di Kota Administrasi Jakarta Timur Mengenai Vaksinasi Pada Kondisi Dengan Komorbid - Hanifah, Laily; Zebua, Eleonara Solomasi (Jurnal Pengabdian Kesehatan Komunitas (Journal of Community Health Service), 2022)
During a COVID-19 pandemic, many government programs have been implemented to reduce COVID-10 cases.  One of the programs is the COVID-19 vaccination. Dasawisma cadres play a role in making the vaccination successful, but unfortunately there were still many cadres who have not participated in the vaccination program. This is a problem, because the cadres who were supposed to be the role models for other citizens, did not vaccinate themselves.  The purpose of this community service is to increase knowledge about vaccination for 437 cadres using the Information, Education and Communication (IEC) method. The activity was carried out online through the Zoom Meeting platform in collaboration with the East Jakarta Sub-Department for Empowerment, Child Protection and Population Control.  The results of the pre-test and post-test showed a p-value of 0.000.  It means that the education provided was useful for increasing the knowledge of cadres about vaccination. It is hoped that further education to cadres will be continued, especially regarding booster vaccination, which are currently being intensified by the government